2009
DOI: 10.1097/wnp.0b013e3181b7f13b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seizures on Cardiac Function

Abstract: Various chronic and acute autonomic effects on the heart are seen during epileptic seizures, and some have been implicated in cases of sudden unexpected death in epilepsy (SUDEP). Chronic autonomic dysfunction, either congenital or acquired through seizures or medications, and structural changes of the heart may all predispose patients to SUDEP. Acute autonomic changes during seizures, in particular ictal bradycardia or transient ischemia, may indicate an increased and preventable risk of mortality in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 116 publications
(148 reference statements)
0
36
1
3
Order By: Relevance
“…30 It is likely that some cases of SUDEP primarily resulted from fatal cardiac arrhythmias, while others primarily resulted from respiratory depression and central apnea. 1,31,32 However, SUDEP related to seizure-induced primary cardiorespiratory failures does not reconcile with the high prevalence of a terminal prone position found in our study. Video-EEG-monitored SUDEP cases have provided us with the most valuable insights into the mechanism of SUDEP.…”
Section: Resultscontrasting
confidence: 79%
“…30 It is likely that some cases of SUDEP primarily resulted from fatal cardiac arrhythmias, while others primarily resulted from respiratory depression and central apnea. 1,31,32 However, SUDEP related to seizure-induced primary cardiorespiratory failures does not reconcile with the high prevalence of a terminal prone position found in our study. Video-EEG-monitored SUDEP cases have provided us with the most valuable insights into the mechanism of SUDEP.…”
Section: Resultscontrasting
confidence: 79%
“…Central modulation of the cardiovascular autonomic nervous system involves a complex network, including the anterior insular cortex, anterior cingulate gyrus, amygdala, and ventromedial prefrontal cortex as detailed in previous publications (Moseley et al, 2013;Schuele, 2009;Schuele et al, 2007a;Surges et al, 2009c). These cortical limbic areas are often involved in the generation and propagation of seizures in patients with refractory temporal lobe epilepsy.…”
Section: Other Manifestations Of Autonomic Dysregulationmentioning
confidence: 97%
“…In 1906, Finny first documented cardiac asystole during a seizure. Since then, a wide range of cardiac arrhythmias have been reported, ranging from atrial fibrillation, supraventricular tachycardia, prolonged QT intervals, and torsades de pointes (Nilsson et al 1997;Nei et al 2004;Schuele 2009;Sevcencu and Struijk 2010). Also, a number of studies have indicated that seizure activity produces cardiac dysfunction and myocardial damage in human patients (Legriel et al 2008;Shimizu et al 2008) as well as animals experiencing seizures that were induced by lethal nerve agents (Tryphonas et al 1996).…”
Section: Introductionmentioning
confidence: 98%